2018
DOI: 10.31219/osf.io/k9p8e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of a parent-implemented language intervention for late-to-talk children: A real-world retrospective clinical chart review

Abstract: Background: Previous research has examined the impact of early language interventions on the linguistic skills of late-to-talk children. However, we have little understanding of how such interventions impact communicative participation (i.e., the ability to communicate in real-world contexts) or what factors influence individual response to these interventions. Aims: (1) To evaluate the effectiveness of Target WordTM – The Hanen Program® for Parents of Children Who are Late Talkers, for improving the communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Despite its strong psychometric properties and initial implementation efforts, the adoption and consistency of use of the FOCUS continued to vary across the 30 PSL Program regions [27,28]. For instance, clinicians at some PSL program regions stopped collecting and reporting FOCUS data.…”
Section: Study Settingmentioning
confidence: 99%
“…Despite its strong psychometric properties and initial implementation efforts, the adoption and consistency of use of the FOCUS continued to vary across the 30 PSL Program regions [27,28]. For instance, clinicians at some PSL program regions stopped collecting and reporting FOCUS data.…”
Section: Study Settingmentioning
confidence: 99%
“…Original 50-item FOCUS (n=20) 13,15,16,[18][19][20][22][23][24][25][26][27][28][29][32][33][34][35][37][38][39] FOCUS-F (n=1) 42 FOCUS-G (n=1) 41 FOCUS-I (n=1) 40 FOCUS-34 (n=2) 20,21 FOCUS Thomas-Stonell et al 15 Case series 4 Thomas-Stonell et al 16 Case series 4 Hidecker et al 19 Case series 4 Kwok et al 20 Case series 4 Cunningham et al 21 Case series 4 Thomas-Stonell et al 22 Case series 4 Washington et al 23 Cohort 3 Washington et al 24 Cohort 3 Namasivayam et al 26 Cohort 3 Pennington et al 27 Case series 4 McLeod et al 28 Randomized trial 2 Namasivayam et al 29 Cohort 3 Washington et al 38 Case series 4…”
Section: Version Usedmentioning
confidence: 99%
“…18 Seven other studies also reported FOCUS scores together with CFCS classifications, included children who were lower-functioning, and documented meaningful change across all CFCS levels. [19][20][21][22][23][24][25] Factors impacting development…”
Section: Version Usedmentioning
confidence: 99%
See 2 more Smart Citations